Efficient and Chiral Electroluminescence from In‐Plane Heterostructure of Transition Metal Dichalcogenide Monolayers (Adv. Funct. Mater. 40/2022). (5th October 2022) - Wada, Naoki; Pu, Jiang; Takaguchi, Yuhei; Zhang, Wenjin; Liu, Zheng; Endo, Takahiko; Irisawa, Toshifumi; Matsuda, Kazunari; Miyauchi, Yuhei; Takenobu, Taishi; Miyata, Yasumitsu
Abstract : Transition Metal Dichalcogenide Monolayers In article number 2203602, Jiang Pu, Taishi Takenobu, Yasumitsu Miyata, and co‐workers report interfacial electroluminescence in in‐plane heterostructures based on transition metal dichalcogenide monolayers. Various combinations of large‐area, highly crystalline in‐plane heterostructures with sharp interfaces are grown by chemical vapor deposition. Significantly, the WS2 /WSe2 in‐plane heterostructures exhibit circularly polarized electroluminescence with polarizability of 10% at room temperature.